Language assessment in practice : developing language assessments and justifying their use in the real world - Bachman, Lyle F., 1944-; Palmer, Adrian S., 1940- (Oxford : Oxford University Press, 2010)
Presents an innovative, unified, and easily applied approach to designing and developing language assessments. Language Assessment in Practice is a follow-up to the bestselling Language Testing in Practice. It allows readers to become competent in the design, development, and use of language assessments. The authors discuss concepts and procedures clearly, illustrated with examples.
Includes bibliographical references (p. [486]-493) and index.
Keywords: Language and languages -- Ability testing; Language and languages -- Study and teaching